Pengembangan LKPD Berbasis Experiential Learning Topik Sistem Persamaan Linear Dua Variabel untuk Memfasilitasi Kemampuan Komunikasi Matematis Peserta Didik Fase D - Hayati, Mella; Suanto, Elfis; Yuanita, Putri (Papanda, 2025)
This research was motivated by the importance of students’ mathematical communication skills. This study aims to develop a Student Worksheet based on the Experiential Learning approach for topic of Systems of Linear Equations in Two Variables, designed to facilitate the mathematical communication skills of Phase D students. The research employed a development method using the 4D model, which consists of four stages: define, design, develop, and disseminate. The subjects of this study were students at Phase D. Six students were involved in the small group trial, and twenty-eight students participated in the large group trial. Data collection was carried out using validation sheets to assess the feasibility of the product and response questionnaires to evaluate its practicality. The instruments used included LKPD validation sheets and practicality questionnaires. The data obtained were analyzed using descriptive quantitative and qualitative methods. Quantitative data were analyzed using percentage formulas to determine the validity and practicality categories, while qualitative data were obtained from validators’ feedback and student responses, which were used to revise and improve the product. The analysis showed that the developed LKPD achieved a validity score of 88.48%, and practicality scores of 88.56% in the small group trial and 87.40% in the large group trial, all of which are categorized as very good. Based on these results, it can be concluded that the Experiential Learning-based LKPD is suitable for use as a learning tool that supports students' mathematical communication skills.